Pelatihan Soft Skills Siswa-Siswi SMKS Mitra Mandiri dalam Memasuki Dunia Kerja - Reni Septrisia; Latifah Hannum Batubara; Lailan Nur Rangkuti; Nur Aliyah NST (Lembaga Pengembangan Kinerja Dosen, 2024)
Vocational High School (SMK) graduates are ready to work in the public/private sector, or work independently as entrepreneurs. Students are given hard skills based on the major they choose and soft skills. However, the need for soft skills is often not given enough attention. This soft skills training and mentoring program for Mitra Mandiri Vocational School students in Panyabungan City aims to make students understand the importance of soft skills. Students are expected to practice applying/using soft skills that support them in finding/creating jobs, writing application letters, writing an interesting, informative and effective Curriculum Vitae (CV). They are also expected to be confident facing job interviews. This program was attended by grade 3 students of Mitra Mandiri Panyabungan Vocational School, leaders and teachers of Mitra Mandiri Panyabungan Vocational School. The training is divided into 2 groups. After training and practice, students are given the opportunity to consult directly (face to face) with the facilitator, and seek information and guidance via WhatsApp and email facilities. The results of the training and mentoring show that students understand the importance of soft skills such as communication skills, self-confidence, respect, open-mindedness, and honesty in the work environment and daily life.